Studi Batang Bawah dan Pengaturan Lingkungannya pada Pembibitan Jarak Pagar (Jatropha Curcas L.) dengan Cara Grafting - Sugiatno Sugiatno; H. Hamim (Jurnal Penelitian Pertanian Terapan, 2010)
The experiment has been conducted in Labuhan Dalam, Tanjung Seneng, Bandar Lampung from January to June 2008. This experiment consisted of 3 subtitles that are: (1)The effect of root stock age and shading degrees on physic nut plant propagation with grafting. Is a factorial experiment (3x4) with split plot design, shading degrees as main plot consisted without shading, light shading), moderate shading, and heavy shading .Root stock age as subplot consisted 6, 8, and 10 weeks after transplanting; (2) The effect of root stock high and scion length on physic nut plant propagation with grafting. Is a factorial experiment (3x3) with randomized completely block design, the first factors were root stock high consisted 10, 15, and 20 cm from nursery medium. The second factors were scion length consisted 5 cm, 7,5 cm, and 10 cm; (3) The effect of kind of bend and IBA concentration on physic nut plant propagation with grafting. Is a factorial experiment (3x3) with randomized completely block design, the first factors were kind of bend consisted raffia rope, plastic rope, and faucet cellophane tape rope. The second factors were IBA concentration consisted 0, 1000, and 3000 ppm. The treatments were consisted 3 replication and each experiment unit consisted 10 seedlings. The result shows that (1) root stock age 8 and 10 weeks produces physic nut seedling growth better than root stock age 6 week. Physic nut seedling without shading and light shading (1 layer paranet) grow better than with moderate shading (2 layers paranet) and heavy shading (3 layers paranet); (2) Root stock high 15 cm produce physic nut seedling growth better than root stock high 10 cm and 20 cm. Length of scion 7,5 cm and 10 cm produces physic nut seedling growth better than length of scion 5 cm; (3) Plastic and faucet cellophane tape rope produce physic nut seedling growth better than raffia rope. IBA concentration 1000 and 2000 ppm produces physic nut seedling growth better than o ppm Keywords: Physic nut, root stock, seedling, grafting